Psychosocial Factors Associated with Smoking Cessation Attempts in Korean High School Students Who Engage in Intermittent and Light Smoking. - Jin Suk Ra; Yeon-Hee Jeong (Child Health Nursing Research, 2020)
Purpose: This study aimed to identify psychosocial factors associated with smoking cessation attempts among Korean high school students who engage in intermittent and light smoking. Methods: Cross-sectional secondary data derived from the 2018 Korea Youth Risk Behavior Web-Based Survey were analyzed within the framework of the biopsychosocial model. The sample comprised 829 high school students who reported current intermittent and light smoking, which was defined as cigarette smoking on 1~29 days in a 30-day period and no more than 10 cigarettes per day. Purposeful selection logistic regression analysis was performed. Results: In total, 71.7% (n=586) of the respondents had tried to stop smoking during the past 12 months. The main result was that respondents who had viewed an anti-smoking advertisement in the past year significantly more smoking cessation attempts than those who had not (adjusted odds ratio=2.59; 95% confidence interval=1.45~4.62, p=.001). Conclusion: To encourage smoking cessation attempts among high school students who engage in intermittent and light smoking, healthcare providers, including school and community nurses, should develop effective interventions using anti-smoking advertisements tailored to adolescents' interests and developmental stage.